Comparison of health‐promoting behaviours, eating behaviour patterns and perceived social support in normal‐weight and overweight pregnant women: An unmatched case-control study - Sepideh Hajian; Azita Fathnezhad‐Kazemi (Wiley, 2020)
Abstract Aim The interventions based on adopting a healthy lifestyle during pregnancy have conflicting results. This study aimed to compare health‐promoting, dietary patterns and social support in normal and overweight pregnant women. Design An unmatched case-control design was used. Methods A total of 360 pregnant women were selected using multistage cluster sampling and divided into two groups of normal and overweight cases. Data were collected using demographic and obstetrics characteristics, health‐promoting lifestyle, perceived social support and eating behaviour questionnaires. Results The evaluation of the health‐promoting behaviours and dietary patterns demonstrated a significant difference between the mean of total scores and their subdomains including self‐actualization, nutrition, consumption of healthy and low‐fat foods, fast food and sweets, as well as emotional eating and accidental planning. There was no significant difference between the two groups about social support.